Pengaruh Customer Review Dan Harga Terhadap Keputusan Pembelian Konsumen Muslim Shopee Di Banjarmasin - Muhammad Abdan Nur; Difi Dahliana (ITB AAS INDONESIA Surakarta, 2023)
The trend of shopping online is increasing, but that does not mean that selling online can be done easily without any obstacles. Sellers who sell online through marketplaces such as Shopee are required to understand what factors can influence purchasing decisions because they have to work harder to get consumers to buy products that consumers cannot see and touch directly. Many studies have been conducted, but Shopee consumers in Banjarmasin have not been studied. Several previous studies have found that prices and customer reviews influence purchasing decisions. However, others find that both have no effect. Therefore, this study aims to describe how the influence of prices and customer reviews on the purchasing decisions of Shopee consumers in Banjarmasin. This survey research uses a questionnaire to collect data and uses the SPSS program to analyze the data. The results showed that simultaneously and partially both had a significant effect on the purchasing decisions of Shopee consumers in Banjarmasin. Finally, because purchasing decisions are a measure of marketing success, the results of this study are expected to be considered for sellers in digital marketplaces in determining marketing strategies.